2016
DOI: 10.1177/0829573516684069
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Students: A GRADE Analysis of the Research on Student Wellness and Classroom Mental Health Support

Abstract: Recommendations derived from research evidence regarding program implementation in school-based mental health [SBMH] require knowledge of the intervention outcomes as well as the potential to translate program components into schools. The Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) analysis was applied to major areas of the SBMH literature in addressing the areas of effectiveness and the strength of recommendation in implementation. Nine areas were addressed: emotional intellige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 120 publications
0
7
0
Order By: Relevance
“…A third macrolevel support refers to various intervention programs aimed at mitigating the impact of youth trauma (Ford, Steinberg, et al, 2012; Scheeringa et al, 2011). Indeed, to synthesize three recent systematic reviews of school-based intervention programs across 171 articles (with some overlapping studies), it appears that long-term programs with a codified curriculum that is co-constructed with caregivers and delivered by trained staff are most effective, although what is still needed are better frameworks for implementing and measuring effectiveness of said programs and protocols for more precise analysis of participant demographics (Rodger et al, 2019; Thomas et al, 2019; Yohannan & Carlson, 2019). Unfortunately, I found that when the primary focus is on investigating the best program intervention, studies minimize underlying racialization problems or imply that race is inconsequential to understanding and responding to students’ trauma-related experiences.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A third macrolevel support refers to various intervention programs aimed at mitigating the impact of youth trauma (Ford, Steinberg, et al, 2012; Scheeringa et al, 2011). Indeed, to synthesize three recent systematic reviews of school-based intervention programs across 171 articles (with some overlapping studies), it appears that long-term programs with a codified curriculum that is co-constructed with caregivers and delivered by trained staff are most effective, although what is still needed are better frameworks for implementing and measuring effectiveness of said programs and protocols for more precise analysis of participant demographics (Rodger et al, 2019; Thomas et al, 2019; Yohannan & Carlson, 2019). Unfortunately, I found that when the primary focus is on investigating the best program intervention, studies minimize underlying racialization problems or imply that race is inconsequential to understanding and responding to students’ trauma-related experiences.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, I found that when the primary focus is on investigating the best program intervention, studies minimize underlying racialization problems or imply that race is inconsequential to understanding and responding to students’ trauma-related experiences. For example, using a race-centered analysis, I found that 85% of the 21 U.S. study samples ( n = 1,359) in Yohannan and Carlson’s (2019) review were composed of students of color; yet almost no intervention programs in the 98 studies Rodger et al (2019) reviewed were specifically designed for students of color.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations